Quality of Life and Depression Conditions of Women with Gestational Diabetes during Pregnancy and Postpartum Period - Reyhan Aydin Doğan; Nezihe Kizilkaya Beji (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective The study was conducted to determine the quality of life and depression of women with gestational diabetes during pregnancy and the postpartum period. Methods 100 pregnant women with gestational diabetes and 100 healthy pregnant women were included in the present study. Data were obtained from pregnant women in their third trimester who agreed to take part in the study. The data was collected during the third trimester and six to eight weeks after the baby was born. The data were obtained by socio-demographic characteristics form, postpartum data collection form, the MOS 36 Item Short Form Health Survey and Center for Epidemiologic Studies Depression Scale (CESD). Results The mean age of pregnant women with gestational diabetes in the study was the same as the average age of healthy pregnant women. The CESD score of pregnant women with gestational diabetes was 26,77 ± 4,85 while the corresponding score was 25,19 ± 4,43 for healthy women. Additionally, the score in the postpartum period was 32.47 ± 5.94 for pregnant women with gestational diabetes and 35.47 ± 8.33 for healthy pregnant women. CESD scores were found to be higher than the cut-off score of 16 in both groups, and the mean scores increased during the postpartum period. Conclusion During the postpartum period, the quality of life of pregnant women with gestational diabetes was affected more negatively than healthy pregnant women. Depressive symptoms of women with both gestational diabetes and healthy pregnancy were found to be high in pregnancy and postpartum periods.